(untitled) (The Review of Diabetic Studies, 2025)
Digital transformation has become a central driver of healthcare safety, prevention, and system resilience. The increasing complexity of care delivery, coupled with emerging infectious threats, medication-related harm, diagnostic errors, and chronic disease burden, has exposed the limitations of fragmented, paper-based, and siloed healthcare systems. Health informatics offers an integrative solution by enabling real-time data capture, interoperability, predictive analytics, and coordinated decision-making across disciplines. This comprehensive narrative review examines digital transformation in healthcare safety and prevention through an interprofessional health informatics framework involving nursing, health security, laboratory services, pharmacy, and public health. Emphasis is placed on clinical surveillance, early warning systems, medication safety, laboratory integration, infection prevention, and population-level risk monitoring. The review highlights how digitally enabled interprofessional collaboration enhances patient safety, strengthens preventive capacity, and supports sustainable health system performance.